2012
DOI: 10.1017/s1049023x12000787
|View full text |Cite
|
Sign up to set email alerts
|

High School Allied Health Students and Their Exposure to the Profession of EMS

Abstract: Overall, there was a lack of exposure to career and educational options in EMS among allied health students in the school system studied, and few students intended to pursue an EMS career after graduation. However, the majority of students indicated they would like to learn more about EMS, and would enroll in an EMT course and ride-along program if available. These findings suggest that, with exposure to the profession, more allied health students could choose EMS as a career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…O'Meara found that students in their first year of study were motivated by their previous experiences with emergency services plus the image of a paramedic's role, adventure and action, and location near family and friends (1). Similarly rural high school students studying an allied health curriculum were more likely to pursue an emergency medical services career if they had exposure to EMS outside of school (20). They were also influenced by the media and thought it would be mentally challenging (20).…”
Section: Discussion (Cont)mentioning
confidence: 99%
See 1 more Smart Citation
“…O'Meara found that students in their first year of study were motivated by their previous experiences with emergency services plus the image of a paramedic's role, adventure and action, and location near family and friends (1). Similarly rural high school students studying an allied health curriculum were more likely to pursue an emergency medical services career if they had exposure to EMS outside of school (20). They were also influenced by the media and thought it would be mentally challenging (20).…”
Section: Discussion (Cont)mentioning
confidence: 99%
“…Similarly rural high school students studying an allied health curriculum were more likely to pursue an emergency medical services career if they had exposure to EMS outside of school (20). They were also influenced by the media and thought it would be mentally challenging (20).…”
Section: Discussion (Cont)mentioning
confidence: 99%
“…3,4 Although beneficial for students to have these options, the omission of a precursor science degree (often approximately 3 years) means that school students may be required to decide on their careers much earlier than before. However, in many cases, there is a lack of career exposure for school students 5,6 and a general lack of awareness of what is required to progress into certain professions. 7 In one study regarding the choice to enter a dietetics program, it was found that most students reported deciding on this career while at university.…”
mentioning
confidence: 99%
“…Although high school minority student pipeline programs are common (46), less has been published in the medical literature regarding college or university-level pipeline programs for medicine (7, 8). Many college and university programs are also focused on increasing medical college admission test (MCAT) scores and grade point averages (GPAs), as the means of increasing acceptance (3).…”
mentioning
confidence: 99%